(untitled) (Islas, 2021)
En este artículo se valora la revista Islas (1958-1968) en su discurso interno bajo las pautas editoriales de Samuel Feijóo, cuando deviene un órgano de difusión de textos e imágenes de las artes visuales regionales, cubanas y foráneas que la hacen merecedora de ser estimada en su real dimensión en la historia del arte en Cuba. Los métodos histórico-lógico, el histórico-crítico y el análisis documental, permiten un acercamiento a la importancia de la revista desde esa perspectiva. The internal discourse in Islas Magazine (1958-1968) is analyzed under Feijoo’s editorial norms since it has turn into a publication for disseminating texts and images of the regional, Cuban and foreign visual arts, that make Islas be esteemed in its full dimension in Cuban art history. The use of the historical-logical and the historical-critical methods as well as documentary analysis allow an approach to the significance of the magazine in that perspective.